MODELS OF THE MODERN SECULAR STATE (American Journal of Research in Humanities and Social Sciences, 2023)
Many countries, with the goal of building a secular democratic state, have different approaches to the issue of creating mechanisms for the implementation of the state's attitude to religion and religious organizations. the article analyzes several models of the modern secular state from this point of view.